High speed rail and airport. Future scenarios in Marco Polo Airport in Venice - Pucci, Paola; Lanza, Giovanni (TeMA - Journal of Land Use, Mobility and Environment, 2019)
This paper introduces an analysis of the possible extension of the catchment area of the Venice Marco Polo Airport, due to the implementation of a direct rail connection and the completion of the high speed/high capacity railway between Milan and Trieste. Both interventions are expected to generate an increase in the accessibility thresholds by rail to the airport. By constructing different scenarios based on the analysis of the evolution in mobility trends and settling patterns, retraced considering both demographic dynamics and large scale projects, this article estimates the effects generated by the new railway connections in terms of extension of the Marco Polo airport’s catchment area and the related impacts on air traffic, in terms of potential new passengers.